2008
DOI: 10.1590/s0103-50532008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Lipid fraction quality evaluation of Brazilian meat-based products

Abstract: A fração lipídica de produtos cárneos foi avaliada através das análises de colesterol, óxidos de colesterol e a composição em ácidos graxos, com ênfase nos isômeros trans. Foram analisados 126 amostras, sendo 45 de produtos cárneos bovinos, 36 de produtos cárneos suínos e 45 de produtos cárneos mistos. O colesterol e os óxidos de colesterol foram determinados por HPLC. A composição em ácidos graxos foi determinada por cromatografia gasosa usando coluna capilar CP-SIL 88. O 7-cetocolesterol (µg g -1 ) foi encon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
3
2
1
Order By: Relevance
“…In fact, the fatty acid composition of sausages of the treatments used in the present experiment differs from sausages made of standard chicken meat and traditional sausages, which lipid fraction derives from beef and pork fat). This difference in composition is shown in Table 6, according to data from Baggio & Bragagnolo (2006) and Baggio & Bragagnolo (2008).The high polyunsaturated fatty acid content of the sausages of the present study presents 4.4 to 5.5 times higher PUFA/SFA ratio than those obtained in commercial sausages, and the values can be compared to the range present in soybean oil (Table 6). …”
supporting
confidence: 67%
See 1 more Smart Citation
“…In fact, the fatty acid composition of sausages of the treatments used in the present experiment differs from sausages made of standard chicken meat and traditional sausages, which lipid fraction derives from beef and pork fat). This difference in composition is shown in Table 6, according to data from Baggio & Bragagnolo (2006) and Baggio & Bragagnolo (2008).The high polyunsaturated fatty acid content of the sausages of the present study presents 4.4 to 5.5 times higher PUFA/SFA ratio than those obtained in commercial sausages, and the values can be compared to the range present in soybean oil (Table 6). …”
supporting
confidence: 67%
“…In fact, the fatty acid composition of sausages of the treatments used in the present experiment differs from sausages made of standard chicken meat and traditional sausages, which lipid fraction derives from beef and pork fat). This difference in composition is shown in Table 6, according to data from Baggio & Bragagnolo (2006) and Baggio & Bragagnolo (2008).…”
Section: Adding Value To the Meat Of Spent Laying Hens Manufacturing mentioning
confidence: 97%
“…Monounsaturated fatty acids (MUFAs) were the major constituent found (mean of 46%), and the major part of these was oleic acid (18:1), ranging from 40.93 to 43.79 %. These proportions was similar to the Brazilian pork products, sausage ("linguiça Toscana"), salami ("Italian type") and traditional and restructured ("presunto" and "apresuntado", respectively) cooked hams, reported by Baggio and Bragagnolo [28]. Greater values of oleic acid are desired for their hypocholesterolemic action because they have the advantage of not reducing the protective high-density (HDL) lipoproteins in human blood.…”
Section: Nutritional Valuesupporting
confidence: 78%
“…Together, these two fatty acids accounted for 22.95% of total fatty acids, being lower than the mean average (~25%) observed by Baggio and Bragagnolo [28] for Brazilian sausages, cooked hams and restructured meat products.…”
Section: Nutritional Valuecontrasting
confidence: 54%
“…Products made with minced cuts are known worldwide as "reconstituted cured-cooked meat products", name adopted in this paper. Baggio & Bragagnolo (2008) compared three types of products: cooked ham, reconstituted cured-cooked meat products and sausage, which are sold in Brazil, and concluded that the cooked ham had the lowest fat content, with results ranging from 2.1 to 3.7%, while the reconstituted cured-cooked meat products showed results between 3.9 and 8.0%, and Tuscan-style sausage had lipid content ranging from 13.4 to 29.0%.…”
Section: Resultsmentioning
confidence: 99%